Phenomenology, Language & Schizophrenia
XII, 389 p.
Keywords: Phenomenology represents a mainstream in the philosophy of subjectivity as well as a rich tradition of inquiry in psychiatry. The conceptual and empirical study of language has become increasingly relevant for psychiatric research and practice. Schizophrenia is still the most enigmatic and most relevant mental disorder. This volume represents an attempt to bring specialists from different fields together in order to integrate various conceptual and empirical approaches for the benefit of schizophrenic research. We hope that it will facilitate discussions among members of such diverse fields as psychiatry, psychology, and philosophy.